Harnessing online digital data in biodiversity monitoring. - Andrea Soriano-Redondo; Ricardo A Correia; Vijay Barve; Thomas M Brooks; Stuart H M Butchart; Ivan Jarić; Ritwik Kulkarni; Richard J Ladle; Ana Sofia Vaz; Enrico Di Minin (PLoS Biology, 2024)
Online digital data from media platforms have the potential to complement biodiversity monitoring efforts. We propose a strategy for integrating these data into current biodiversity datasets in light of the Kunming-Montreal Global Biodiversity Framework.